Phanerozoic Evolution of Lithospheric Structures of the North China Craton. Issue 6 (26th March 2022) - Xu, Yixian; Zhang, Yi; Yang, Bo; Bao, Xuewei
Abstract: Modification of the cratonic lithosphere remains no consensus on the mechanisms. We here presented a method to reconstruct the Paleozoic‐lithospheric structures of the North China Craton (NCC) from its current structures. The results show that, after the Paleozoic, massive thinning only occurred in the eastern East Block (EB) but thickening presented in the northern Ordos Basin and the region from the Weibei uplift to South Taihang Mountains uplift. We also calculated the self‐sustaining oscillation periods of three parts in the NCC during the course of feedback between the thermal and mechanical equilibrium. The periods are in good agreement with the periodicity reflected in the sedimentation rate of the Ordos Basin and basaltic underplating events in the Trans‐North China Orogen. Based on the presenting results, we argue that, except the EB, the Phanerozoic lithospheric modification of the NCC is mainly controlled by heat conduction and dissipation through the cratonic lithosphere. Plain Language Summary: Cratons are ancient continents that have generally been undeformed and tectonically stable for long periods of time, often since about 2.5 Ga ago. The North China Craton (NCC) remained a stable craton in the 480 Ma due to its lithosphere as thick as ∼200 km, determined from the xenoliths from the kimberlites. However, recent studies show that significant parts of the NCC lithosphere have been modified. In particular, the lithosphere of the East Block of the NCC has been thinned to only ∼70 km, which is much thinner than the thickness of a typical cratonic lithosphere. We here adopted the method based on isostacy theory to reconstruct the lithospheric thickness before this modification from its present thickness. The result shows that lithosphere modification of the NCC is significantly non‐uniform. The thickness changes in main parts of the NCC can be explained by a self‐sustaining oscillation behavior driven only by deep heat flow out of the Earth. By integrating of studies from the African and North American cratons, we further proposed that both mantle‐plume impingement and oceanic plate subduction are secondary factors that can alter the vertical self‐sustaining oscillation periods of the ancient continents. Key Points: Lithospheric thickness of the North China Craton (NCC) in the Paleozoic is estimated Different deformation mechanisms in different domains of the NCC are presented Driving forces for lithospheric modification are mainly heat conduction and dissipation through the cool cratonic lithosphere